Oxford Handbooks Online 2014
DOI: 10.1093/oxfordhb/9780199381708.013.19
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Anxiety and Depression with Substance Use Disorders

Abstract: The comorbidity of substance use disorders (SUDs) with anxiety and depression is the focus of substantial research attention and approached from myriad perspectives. This chapter focuses on the resultant complex research literature, first providing an overview of epidemiologic studies that have examined the prevalence of co-occurrence of SUDs (including alcohol and other drug use disorders) with anxiety and depressive disorders, as well as clinical correlates of these forms of comorbidity. Next, theoretical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…One of these suggested that SUD patients often expose themselves to dangerous or trauma-prone environments (high-risk hypothesis; Stewart & Conrod, 2008). It was assumed that when this trauma exposure happens after initial substance use, substance use aggravates.

And, indeed, you meet severely addicted people who often expose themselves to dangerous situations which increases the risk for trauma.

…”
Section: Resultsmentioning
confidence: 99%
“…One of these suggested that SUD patients often expose themselves to dangerous or trauma-prone environments (high-risk hypothesis; Stewart & Conrod, 2008). It was assumed that when this trauma exposure happens after initial substance use, substance use aggravates.

And, indeed, you meet severely addicted people who often expose themselves to dangerous situations which increases the risk for trauma.

…”
Section: Resultsmentioning
confidence: 99%
“…Common practice typically encourages patients with comorbid substance use and mental health problems to seek addiction treatment first, a practice that may lead to untreated mental health problems (17). Recent models suggest that treating anxiety and alcohol use disorders in an integrated approach may be preferable both from clinical (7, 2022) and public health perspectives, as this model is in line with recommendations from the Affordable Care Act (23–25). …”
mentioning
confidence: 78%
“…Providing treatment for the underlying negative affect may prevent alcohol problems from persisting and worsening. This is an area of growing research attention, which has led to the development of models aiming to treat alcohol and anxiety concurrently (2022). Still, ongoing efforts have focused on providing joint treatment to patients primarily seen as alcohol patients in alcohol treatment settings.…”
Section: Discussionmentioning
confidence: 99%
“…High comorbidity rates exist between SUD and AD. [35][36][37] Studies had shown that high AD is related to increased use of substances, increased severity of alcohol withdrawal, and higher relapse rates following substance abuse treatment, 15,[38][39][40] as well as HADDAD ET AL.…”
Section: Discussionmentioning
confidence: 99%